Clamping-mediated incorporation of single-stranded DNA with concomitant DNA synthesis by Taq polymerase involves nick-translation - Yoshiyuki Ohtsubo; Syoutaro Kawahara; Yuji Nagata (Scientific Reports, 2024)
Abstract The development and characterization of a new enzyme reaction contribute to advancements in modern biotechnology. Here, we report a novel CIS (clamping-mediated incorporation of single-stranded DNA with concomitant DNA synthesis) reaction catalyzed by Taq polymerase. In the reaction, a single-stranded DNA (ssDNA) with 3′ Cs is attached with a preformed 3′ G-tail of double-stranded DNA (dsDNA); DNA syntheses starting from both 3′ ends result in the incorporation of ssDNA. A 3′ G-tail length of 3 nucleotides adequately supports this reaction, indicating that Taq polymerase can clump short Watson–Crick base pairs as short as three pairs and use them to initiate DNA polymerization. The reverse transcriptase from Molony murine leukemia virus catalyzes strand displacement synthesis and produces flapped-end DNA, whereas the reaction by Taq polymerase involves the nick translation. These new reaction properties may be beneficial for the development of new molecular tools applicable in various fields. Apart from its CIS reaction activity, we also report that Taq polymerase has the undesirable characteristic of removing 5' fluorescent labels from dsDNA. This characteristic may have compromised various experiments involving the preparation of fluorescently-labeled dsDNA by PCR for a long time.